2009
DOI: 10.1038/jid.2008.327
|View full text |Cite
|
Sign up to set email alerts
|

BH3 Mimetic ABT-737 and a Proteasome Inhibitor Synergistically Kill Melanomas through Noxa-Dependent Apoptosis

Abstract: The Bcl-2 family is important in modulating sensitivity to anticancer drugs in many cancers, including melanomas. The BH3 mimetic ABT-737 is a potent small molecule inhibitor of the anti-apoptotic proteins Bcl-2/Bcl-X(L)/Bcl-w. In this report, we examined whether ABT-737 is effective in killing melanoma cells in combination with the proteasome inhibitor MG-132, and further evaluated the mechanisms of action. Viability, morphological, and Annexin V apoptosis assays showed that ABT-737 alone exhibited little cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 35 publications
(56 reference statements)
6
51
1
Order By: Relevance
“…Indeed, our findings support this prediction by demonstrating that that the combination of BH3-M6 with the proteasome inhibitor CEP-1612 synergistically kills A549 cells. Our results are consistent with others that show that ABT-737 synergizes with the proteasome inhibitors bortezomib (50) or MG-132 (51).…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, our findings support this prediction by demonstrating that that the combination of BH3-M6 with the proteasome inhibitor CEP-1612 synergistically kills A549 cells. Our results are consistent with others that show that ABT-737 synergizes with the proteasome inhibitors bortezomib (50) or MG-132 (51).…”
Section: Discussionsupporting
confidence: 83%
“…42,43 Recent studies indicated that BH3-mimetics can be used to treat nonlymphoid cancers but mostly in combination with oestrogen antagonists, proteasome inhibitors, specific PI3K-mTOR inhibitors or chemotherapy. 24,[44][45][46][47][48][49] As previous findings from our laboratory demonstrated that E-cadherin-negative lobular breast cancer depends on p120-catenin-mediated activation of RhoA, Rock and subsequent actomyosin contraction, 26 we anticipate that dual inhibition of these pathways might be successful in E-cadherin-negative cancers that are not driven by oncogenic activation of GFR pathways. Although we do not yet know whether RhoA-Rock signals converge onto the GFR-AKT-FOXO axis in the regulation of anoikis resistance, the fact that FOXO expression had no effect on survival of B-RAF/KRAS-mutated MDA-MB-231 cells seems to be in line with this assumption.…”
Section: Discussionmentioning
confidence: 95%
“…11 The efficacy of ABT-737 has already shown in vitro inducing apoptosis of carcinoma and AML cell lines, 12 ex vivo on patients' blasts, 11 in vivo on a mouse model of lymphoma 13 and on a xenograft model of small cell lung cancer. 14 The combination of ABT-737 with chemotherapeutic agents [15][16][17] or other targeted therapy molecules 18,19 has synergistic efficacy. A related orally bioavailable derivative, ABT-263 (Navitoclax) has been tested in a phase I clinical trial on patients with both small cell lung cancer and other solid tumors 20,21 and chronic lymphocytic leukemia 22,23 in which acceptable toxicity and promising efficacy has been reported.…”
Section: Introductionmentioning
confidence: 99%